Case Report: Open reduction and fixation of Pipkin type IV femoral head fracture through minimally invasive direct anterior approach - Zalewski, Andrzej; Pastuszak, Mateusz; Chai, Jongmin; Jopowicz, Robert; Kawka, Mateusz; Skowronek, Paweł (Frontiers in Surgery, 2026)
The authors present the case of a 60-year-old patient with a Pipkin type IV femoral head fracture treated surgically with open reduction and internal fixation (ORIF) using a minimally invasive direct anterior approach (MIS DAA). The patient sustained the injury in a motorcycle accident, and imaging revealed a displaced fracture of the femoral head with involvement of the posterior acetabular wall. A decision was made for surgical treatment using MIS DAA to minimize the risk of complications. The procedure was performed through an anterior approach. Intraoperatively identified free bone fragments from the posterior acetabulum wall were removed due to a high degree of comminution, and the fracture was stabilized with Herbert screws. Postoperatively, antithrombotic prophylaxis and rehabilitation were implemented. In the postoperative period, a complication in the form of deep vein thrombosis was observed, which was effectively managed. Twelve months after the operation, the patient returned to physical activity, experienced no pain, and the range of motion in the hip joint improved and consisted for 3 years of follow-up. Functional assessment using the FJS-12 scale showed gradual improvement. The use of MIS DAA in the treatment of Pipkin type IV femoral head fracture allowed for a good clinical result and avoidance of complications such as avascular necrosis of the femoral head and heterotopic ossification. This technique may be an effective alternative to traditional methods of treating this type of fracture.